Model selection for merger and acquisition analysis in Asian emerging markets. (2016) - Ma, Jianyu; Geng, Mingzhai; Chu, Yun
We extract a dataset of mergers and acquisitions from Asian emerging markets and examine the distribution of the stock returns for the acquiring firm and the corresponding market portfolio in each deal. Non-normal distribution of the returns appears in the test of most deals. We use two robust regressions and a nonparametric statistic test to examine the efficacy of the standard OLS market model. The traditional methods of measuring abnormal returns (ARs) around event windows may be flawed. The robust regressions, Huber regression M-estimator and bootstrapping quantile regression, provide better and higher estimation of abnormal returns.